Evaluasi Kadar Kreatinin dan Mikroalbumin dengan HbA1C - Suryanata Kesuma; Sresta Azahra; Amalia Diah Suci Rahmah (Borneo Journal of Medical Laboratory Technology, 2023)
Diabetes Mellitus (DM) is a metabolic disease caused by high blood glucose levels (hyperglycemia). Hyperglycemia is caused due to lack of insulin secretion in the body. Glycemic control in diabetic patients is seen in HbA1C levels. One of the complications of DM is diabetic nephropathy. Renal function abnormalities associated with diabetic nephropathy are indicated by increased levels of creatinine and microalbumin. This shows that it is necessary to monitor kidney function in DM. Monitoring DM patients with HbA1C levels <6.5% is desirable, with these levels indicating that glycemic control is good. This study aimed to determine the relationship between creatinine and microalbumin levels with HbA1C <6.5% in Diabetes Mellitus patients in Samarinda. This type of research is analytic with a cross-sectional design. Spearman correlation statistical test. The sample of this study was 107 DM patients with HbA1C levels <6.5% who did medical checkups at the Media Farma Clinic, Samarinda. Sampling is done by Total Sampling. HbA1C examination method with turbidimetry. Method of checking creatinine by Jaffe reaction. Method of examination of microalbumin with immunoturbidimetry. All parameters are quality controlled before measurement. The measurement results were validated by a clinical pathologist. The results showed that the correlation of creatinine with HbA1C <6.5% obtained p value = (0.826), microalbumin with HbA1C <6.5% obtained p value = (0.146), and creatinine with microalbumin obtained p value = (0.082). All these results indicate that H0 is accepted and Ha is rejected. This study concludes no significant relationship exists between creatinine and microalbumin values with HbA1C levels <6.5% in Diabetes Mellitus in Samarinda, especially Media Farma Clinic.